2007
DOI: 10.1088/1748-6041/2/2/012
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatibility evaluation of hydroxyapatite/collagen nanocomposites doped with Zn +2

Abstract: In this work, novel composites based on calcium phosphates (CaP)/collagen (COL) doped with Zn(+2) have been synthesized. They were characterized by SEM coupled to EDS microprobe in order to evaluate their morphology and chemical composition, respectively. The biocompatibility of these synthetic CaP/COL nanocomposites doped and undoped with Zn(+2) was investigated through osteoblast cell culture assay. Calcium phosphates were produced via aqueous precipitation routes where two different phases were obtained, hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 20 publications
2
30
0
2
Order By: Relevance
“…8e,f), it could be concluded that hydroxyapatite phase was formed on the surface of synthesized hybrid materials. On the other hand, it can be observed accumulation of HA on the surface of collagen fibrils, which was in good correspondence to the data, obtained by other authors working in the field of biomimetric mineralization of collagen fibrils [46,62,65,[70][71][72]. …”
Section: Resultssupporting
confidence: 91%
“…8e,f), it could be concluded that hydroxyapatite phase was formed on the surface of synthesized hybrid materials. On the other hand, it can be observed accumulation of HA on the surface of collagen fibrils, which was in good correspondence to the data, obtained by other authors working in the field of biomimetric mineralization of collagen fibrils [46,62,65,[70][71][72]. …”
Section: Resultssupporting
confidence: 91%
“…40,67,68,[74][75][76] Regarding cytotoxicity testing, the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay is the most popular. MTT is a standard colorimetric assay for measuring cellular growth.…”
Section: Foreign Body Reactionmentioning
confidence: 99%
“…The extensive use of collagen in medicine, dentistry, and pharmacology is also related to its natural properties, including hemostatic activity, biodegradability, low allergenicity with high antigenicity and biocompatibility [8]. Furthermore, it is an efficient porous matrix (scaffold) with specific physical, chemical, and biological features that are of interest for multiple bioengineering and cell culture applications [9][10][11][12][13][14][15]. Type I collagen is currently the gold standard in the field of tissue-engineering [14].…”
Section: Introductionmentioning
confidence: 99%